Molten metal jetting for repairing aluminum components - Benedikt Kirchebner; Kellen D. Traxel; Alexander E. Wilson-Heid; Eric S. Elton; Andrew J. Pascall; Jason R. Jeffries (Additive Manufacturing Letters)
Molten metal jetting (MMJ) is an additive manufacturing (AM) method where droplets of molten metal are used to build parts. Like most AM technologies, MMJ is typically used to build stand-alone parts rather than add onto existing parts. However, the droplet-wise deposition method of MMJ is inherently compatible with the ability to build on existing parts. Here, we utilize MMJ to “repair” machined damage on cast aluminum parts. A commercial MMJ system was used to fill in varied but defined groove geometries to find optimal shapes amenable to repair with MMJ. Subsequently, grooves were cut into tensile specimens and back-filled (repaired) using MMJ. Tensile tests indicate that MMJ repair restores significant strength to samples despite the distinct microstructure and void structures present in the repaired section. Repaired samples demonstrated tensile strengths ∼72 % of the as-received material, compared to UTS of ∼33 % for damaged samples. These results indicate that MMJ is a viable method to repair parts where other repair methods may be impractical.